The Effect of Compensation on Job Satisfaction of Regional Public Service Agency (BLUD) Nurses and Organizational Citizenship Behavior (OCB) at RSUD Bayu Asih Purwakarta - Adam BachtiaR; Suhat S.; Ayu Laili Rahmiyati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Organizational Citizenship Behavior (OCB) is the behavior of employees that goes beyond their formal obligations, is very important in supporting organizational performance. Good job satisfaction is often associated with increased OCB, while compensation is a key factor in influencing employee job satisfaction. This study was conducted at RSUD Bayu Asih Purwakarta, especially for BLUD nurses, to determine the effect of compensation on job satisfaction and its impact on OCB. Objective: This study aims to analyze the effect of compensation on job satisfaction and Organizational Citizenship Behavior (OCB) in BLUD nurses at RSUD Bayu Asih Purwakarta. Methods: This study used quantitative methods with a cross-sectional approach. The study was conducted from March-September 2024. Data were collected from 76 BLUD nurses at RSUD Bayu Asih Purwakarta through questionnaires. Analysis of research data using univariate analysis explains the characteristics of variables, while bivariate analysis examines the influence between variables using chi-square. This study uses path analysis to test the causal relationship between variables that have been determined bivariate. Data processing was carried out with the SPSS version 25 statistical program. Results: The results showed that there was a significant influence between compensation and nurses' job satisfaction, indicated by a p-value of 0.001 (<0.05). In addition, compensation also has a significant influence on the application of OCB with a p-value of 0.005 (<0.05). The effect of job satisfaction on OCB is also significant with a p-value of 0.000 (<0.05). The contribution of the effect of compensation on job satisfaction and its impact on OCB is 43.9%, indicating the important role of job satisfaction as a mediator in this relationship. Conclusion: Adequate compensation can increase nurses' job satisfaction and Organizational Citizenship Behavior (OCB). Hospital management needs to increase compensation and improve supervisor-subordinate relationships to foster job satisfaction, so that voluntary behaviors such as OCB can develop, improving overall organizational performance.